Investigation of Interface States in Si/NAOS-SiO2/HfO2 Structures Using Complete Acoustic Spectroscopy - Peter Bury; Taketoshi Matsumoto; Stefan Hardon; Ivan Bellan; Marian Janek; Hikaru Kobayashi (Communications - Scientific letters of the University of Zilina, 2018)
The set of MOS structures formed on n-type Si substrate with (NAOS)-SiO2/HfO2 gate dielectric layers was prepared and annealed in N2 atmosphere at various temperatures to stabilize the structure and to decrease the interface states density. Two Acoustic DLTS techniques using both surface (SAW) and longitudinal (LAW) acoustic waves including acoustoelectric response signal versus gate voltage dependence (Uac-Ug characteristics) were used to characterize the interface states and the role of annealing treatment. The main interface deep centers with activation energies about 0.30 and 0.20 eV, typical for dangling bonds were observed as well as a particular influence of annealing treatment on the interface states. The obtained results are analyzed, discussed and mutually compared.